Abscisic Acid Regulation of DC8, A Carrot Embryonic Gene - Hatzopoulos, Polydefkis (1990)
DC8 encodes a hydrophylic 66 kilodalton protein located in the cytoplasm and cell walls of carrot (Daucus carota) embryo and endosperm. During somatic embryogenesis, the levels of DC8 mRNA and protein begin to increase 5 days after removal of auxin. To study the role of abscisic acid (ABA) in the regulation of DC8 gene, fluridone, 1-methyl-3-phenyl,-5(3-trifluoro-methyl-phenyl)-4(1H)-pyridinone, was used to inhibit the endogenous ABA content of the embryos. Fluridone, 50 micrograms per milliliter, effectively inhibits the accumulation of ABA in globular-tage enbryos. Western and Northern analysis show that when fluridone is added to the culture medium DC8 protein and mRNA decrease to very low levels. ABA added to fluridone supplemented culture media restores the DC8 protein and mRNA to control levels. Globular-stage embryos contain 0.9 to 1.4 × 10(−7) molar ABA while 10(−6) molar exogenously supplied ABA is the optimal concentration for restoration of DC8 protein accumulation in fluridone-treated embryos. The mRNA level is increased after 15 minutes of ABA addition and reaches maximal levels by 60 minutes. Evidence is presented that, unlike other ABA-regulated genes, DC8 is not induced in nonembryonic tissues via desiccation nor addition of ABA.